Listening to Bedouin Women Who Were Affected by Intimate Partner Violence and Sought Help From a Doctor - Manor-Binyamini, Iris (Journal of interpersonal violence, 2021)
The purpose of this study was to examine how Bedouin women perceived and interpreted seeing a doctor for help in the aftermath of intimate partner violence. In the phenomenological study, 38 semi-structured interviews were conducted at two different points in time. The first interview took place before the first appointment with the doctor, and the second took place about 3 months after seeing the doctor. The findings revealed two main themes: an act of resistance against the prevailing social norms and empowerment out of crisis. The study found that doctors and other professionals working in the field of domestic violence in community clinics provide a reliable first source of support for women within a limiting social space. This brings into focus the centrality of the role of the doctor/health care professionals within the framework of the community clinic and is intended to direct, train, and deepen the insights of the medical staff that work with women affected by intimate partner violence and to create uniformity in the interventions for these women.